Ship resistance when operating in floating ice floes: Derivation, validation, and application of an empirical equation. (September 2021) - Huang, Luofeng; Li, Zhiyuan; Ryan, Christopher; Ringsberg, Jonas W.; Pena, Blanca; Li, Minghao; Ding, Li; Thomas, Giles
Abstract: With the effects of global warming, the Arctic is presenting a new environment where numerous ice floes are floating on the open sea surface. Whilst this has improved Arctic shipping navigability in an unprecedented way, the interaction of such floes with ships is yet to be understood to aid the designing of ships and route planning for this region. To further explore this topic, the present work develops a procedure to derive an empirical equation that can predict the effects of such floes on ship resistance. Based on a validated computational approach, extensive data are extracted from simulations of three different ships with varying operational and environmental conditions. The ice-floe resistance is shown to strongly correlate with ship beam, ship buttock angle, ship waterline angle, ship speed, ice concentration, ice thickness and floe diameter, and the regression powers of each of the parameters on resistance are ascertained. This leads to a generic empirical equation that can swiftly predict ice-floe resistance for a given ship in a given condition. Subsequently, demonstrations are given on the incorporation of the derived equation into a set of real-time Arctic ship performance model and voyage planning tool, which can predict a ship's fuel consumption in ice-infested seas and dynamically suggest a route with the least safety concern and fuel consumption. Moreover, the equation is validated by providing ice resistance prediction for experimental and full-scale conditions from multiple sources, showing high accuracy. In conclusion, the empirical equation is shown to give valid and rapid estimates for ice-floe resistance, providing valuable insights into ship designs for the region, as well as facilitating practical applications for polar navigation. Highlights: A procedure is developed to derive an empirical equation to rapidly predict ship resistance induced by floating ice floes. Multiple sources of model tests and full-scale measurements are used to validate the empirical equation. The derived equation is incorporated into a set of new tools - Arctic ship performance model and voyage planning tool. The tools can inform a ship's fuel consumption in ice-infested seas and perform route planning on a real-time basis.